Applying ‘mixed methods’ in the study of tourist behaviours in the city – an example of conceptualization and application (discursive article) - Kotus, Jacek; Rzeszewski, Michał (Turyzm/Tourism, 2015)
This article fits into the category of a conceptual-discursive article. Its aim is to discuss the application of ‘mixed methods’ in research concerning tourist behaviours, especially in the city. The article consists of a part presenting a set of methods used to study such behaviours and a part discussing the results concerning the application of a proposed research procedure algorithm. The authors take a behavioural approach and propose using a quasi-experimental method combined with techniques of mobility monitoring (GPS), and the qualitative methods used in sociological research. The article presents a discussion concerning ‘mixed methods’, discusses a proposed algorithm of research procedure and presents conclusions following the joint application of these methods.